Treatment of Palatally Displaced Canines Using Miniscrews for Direct or Indirect Anchorage: A Three-Dimensional Prospective Cohort Study on Tooth Movement Speed - Marco Migliorati; Sara Drago; Tecla Bocchino; Ambra Michelotti; Vincenzo D’Antò (Applied Sciences, 2022)
Palatally impacted canines are usually challenging to treat in terms of both biomechanics and possible side effects. Different therapeutic approaches have been reported with or without the use of temporary anchorage devices, including the canine-first approach. Two groups of patients with palatally impacted canines were compared, observing their canine movement measured on consecutive CBCTs after three months of treatment. In the control group, impacted canines were treated with direct anchorage on miniscrews, and in the test group with indirect anchorage using a miniscrew-supported transpalatal arch. The primary outcome was the canine movement speed; the secondary outcome was the change in the root length of adjacent teeth. The median monthly apex speed was 1.05 mm in the control group (IR [0.74, 1.64]) and 0.72 mm in the test group (IR [0.27, 1.30]). The median monthly cusp displacement was 1.89 mm in the control group (IR [1.04, 2.84]) and 1.08 mm in the test group (IR [0.81, 1.91]). Approximately 50% of teeth adjacent to an impacted canine underwent a negative root length change of less than 1 mm in the majority of cases, but no significant differences were found in root length changes between groups. No statistically significant differences in the reported speeds were found, and no miniscrew failures were observed in either group.